Factors influencing student choice : A study of a Malaysian Public University - Peter, Songan; Hong, Kian Sam; Gabriel, Tonga; Mustafa, Abdul Rahman; Tan, Kok Wah (Asian Centre for Research on University Learning and Teaching (ACRULeT), 2010)
This paper discusses a study of the information sources employed by students to get information regarding University Malaysia Sarawak (UNIMAS) and also the factors influencing students' choice of UNIMAS. In addition, differences in sources of information and factors of influence based on types of faculty and selected student demographics were also examined. This crosssectional survey research was carried out with a sample consisting of 1,396 first-year students in UNIMAS. The findings of the study showed that "Word of mouth through friends and relatives" and "UNIMAS website" were the two main sources of information. Furthermore, "Academic Program Choice ", "Quality of Teaching and Academics", "Employment Prospect" and "University Choice" were factors contributing towards students selecting UNIMAS to pursue their studies. Inferential statistical analyses consisting of independent t-tests and One-way ANOVA yielded mixed results that could have implications for UNIMAS and other public higher education institutions in employing appropriate strategies to target different segments of prospective students.